Gorham–Stout disease with life-threatening pleural effusion treated with a pleuro-peritoneal shunt: a case report. (1st June 2022) - Toivonen, Leevi A; Neva, Marko H; Sioris, Thanos; Isomäki, Pia; Metso, Saara
Abstract : Summary: Gorham–Stout disease (GSD) is a rare bone disease characterized by massive osteolysis and lymphatic proliferation. The origin of the condition is unknown, and no established treatment protocol exists. Massive pleural effusion is a frequent complication of GSD in the thoracic region. We present the case of a 23-year-old male with thoracic GSD, subsequent paraparesis, and life-threatening pleural effusion. The patient was managed by a multidisciplinary team with a good recovery. The pleural effusion was successfully treated with a pleuro-peritoneal shunt. This is the first report of the use of this mini-invasive technique in the management of pleural effusion related to GSD. Further, we present the potential role of interleukin-6 and bone resorption markers in the measurement of the disease activity. Learning points: Multidisciplinary approach is important in the management of rare and severe disorders such as Gorham-Stout disease. Pleuro-peritoneal shunting is a valuable option in the treatment of pleural effusion related to GSD. Interleukin-6 and bone resorption markers appear useful in measuring the disease activity of GSD.